Los espacios libres de la ciudad de Zaragoza, en la perspectiva de la educación ambiental - Bernad Mainar, Juan Antonio; Bello Muñoz, María Teresa; Cabeza Garrido, Fernando; Porta Royo, Isabel; Gascón Villarroya, Amalia (Geographicalia, 2017)
.